A Schema-Activation Approach to Failure and Success in Self-Control - Bertrams, Alex (Frontiers in Psychology, 2020)
Numerous studies confirm the so-called ego depletion effect (i.e., self-control is impaired after an initial unrelated self-control task). During recent years, the criticism on this limited-resource approach to willpower has increased, and alternative models have been developed. I argue that the existing models cannot explain the variety of results found in the ego depletion literature and introduce the schema model of self-control. Referring to related schema conceptions (i.e., illness schemas and emotion schemas), I posit that the processes that cause ego depletion effects occur around the activation of the fatigue/decreased vitality schema. This schema becomes activated via the registration of behavioral and physiological changes related to exercising self-control. The activation of the schema should instigate the motivation to conserve energy and, therefore, cause reduced effort and decreased performance in a subsequent self-control task. Moderator variables (e.g., energy supply) should influence the (non)activation of the fatigue/decreased vitality schema or its consequences.